Negative emotion modulates prefrontal cortex activity during a working memory task: a NIRS study - Ozawa, Sachiyo; Matsuda, Goh; Hiraki, Kazuo (Frontiers in Human Neuroscience, 2014)
This study investigated the neural processing underlying the cognitive control of emotions induced by the presentation of task-irrelevant emotional pictures before a working memory task. Previous studies have suggested that the cognitive control of emotion involves the prefrontal regions. Therefore, we measured the hemodynamic responses that occurred in the prefrontal region with a 16-channel near-infrared spectroscopy (NIRS) system. In our experiment, participants observed two negative or two neutral pictures in succession immediately before a 1-back or 3-back task. Pictures were selected from the International Affective Picture System. We measured the changes in the concentration of oxygenated hemoglobin (oxyHb) during picture presentation and during the n-back task. The emotional valence of the picture affected the oxyHb changes in anterior parts of the medial prefrontal cortex (located in the left and right superior frontal gyrus) and left inferior frontal gyrus during the n-back task; the oxyHb changes during the task were significantly greater following negative rather than neutral stimulation. As indicated in a number of previous studies, and the time courses of the oxyHb changes in our study, activation in these locations is possibly led by cognitive control of emotion, though we cannot deny it may simply be emotional responses. There were no effects of emotion on oxyHb changes during picture presentation or on n-back task performance. Although further studies are necessary to confirm this interpretation, our findings suggest that NIRS can be used to investigate neural processing during emotional control.